The pre‐efficacy phase testing for PAfitME™—A behavioral physical activity intervention to manage moderate and severe symptoms among advanced stage cancer patients - Wang, Hsiao‐Lan; Donovan, Kristine A.; Rajasekhara, Sahana; Padhya, Tapan; Buck, Harleah G.; Szalacha, Laura; Chang, J. Morris; Brown, Jaelyn D.; Smith, Barbara (Research in nursing & health, 2021)
Fatigue and pain are the most frequently reported symptoms among advanced‐stage cancer patients. Although physical activity (PA) is known to improve the aforementioned symptoms, few patients demonstrate the physically active behavior that adheres to the clinical guidelines regarding PA. The current article presents an exemplar that used the National Institute of Health's Obesity‐Related Behavioral Intervention Trial (ORBIT) model and developed a behavioral intervention known as the personalized Physical Activity intervention with fitness graded Motion Exergames (PAfitME™). There were two phases of testing in the ORBIT model presented in the current paper. In Phase I testing, a standardized exergame prescription was evaluated by an advisory board and a single‐case study was used to evaluate the personalized exergame prescription with personalization of the fitness levels. In Phase IIa, a within‐group pre‐ and posttest design was used to evaluate the personalized exergame prescriptions with personalization of the fitness levels, self‐efficacy, and variation in fatigue/pain. Subsequently, a complete intervention package was developed in accordance with a logic model, driven from the result of the Phase IIa testing with clinically significant findings. Currently, PAfitME™ is under Phase IIb testing in a randomized clinical trial with a control group. PAfitME™ employs a personalized approach to initiate and promote physically active behavior, to facilitate the management of fatigue and pain in cancer patients. Positive results from an efficacy trial would support the use of PAfitME™ in the management of fatigue and pain in advanced‐stage cancer patients.